2020
DOI: 10.35631/ijppsw.27006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Servant Leadership Towards Organizational Citizenship Behaviour (Ocb) and Job Satisfaction Among Teachers: A Review of Literature

Abstract: This paper examines the relationship between servant leadership, organizational citizenship behavior, and job satisfaction among school teachers. The first objective of the study is to explore the history, concept, and development of servant leadership, organizational citizenship behavior, and job satisfaction. The second objective is to determine previous related studies that reveal the relationship between these 3 theories towards teachers throughout the world. The third objective of the study is to focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the field of education, leadership behaviour is one of the factors that have a significant relationship with teacher OCB (Febriantina et al, 2021;Kumar et al, 2022;Shie & Chang, 2022;Shofiyuddin, 2021). However, research on the relationship between servant leadership and teacher OCB was found to be lacking (Shamsuddin et al, 2020), despite the fact that this leadership style was found to be preferred by teachers and more effective than authoritative leadership due to the better use of the leader's power (Zhang et al, 2012). Furthermore, servant leadership has an advantage over transformative leadership in that it provides more opportunities for passive followers (Shamsuddin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of education, leadership behaviour is one of the factors that have a significant relationship with teacher OCB (Febriantina et al, 2021;Kumar et al, 2022;Shie & Chang, 2022;Shofiyuddin, 2021). However, research on the relationship between servant leadership and teacher OCB was found to be lacking (Shamsuddin et al, 2020), despite the fact that this leadership style was found to be preferred by teachers and more effective than authoritative leadership due to the better use of the leader's power (Zhang et al, 2012). Furthermore, servant leadership has an advantage over transformative leadership in that it provides more opportunities for passive followers (Shamsuddin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the relationship between servant leadership and teacher OCB was found to be lacking (Shamsuddin et al, 2020), despite the fact that this leadership style was found to be preferred by teachers and more effective than authoritative leadership due to the better use of the leader's power (Zhang et al, 2012). Furthermore, servant leadership has an advantage over transformative leadership in that it provides more opportunities for passive followers (Shamsuddin et al, 2020). In addition to leadership, dispositional factors such as individual differences play an important role in predicting employees' proclivity to exhibit OCB (Organ, 1990).…”
Section: Introductionmentioning
confidence: 99%